Analisis Gaya Kepemimpinan Narendra Modi Terhadap Perubahan Kebijakan Luar Negeri Look East ke Act East - Iqbal Anta Maulana; Muhammad Faizal Alfian (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
In 2014 Indian Prime Minister Narendra Modi made the Act East foreign policy as a replacement for the previous policy, Look East. This policy is oriented towards strengthening the relationship between economic cooperation and maritime security in the Asia Pacific region in response to China's dominance in the Indian Ocean and South China Sea regions. This study will analyze Narendra Modi's type of leadership style to answer the question